5.20.8 Problems 701 to 800

Table 5.921: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

2723

\[ {}y^{\prime \prime \prime \prime }-y = t +\sin \left (t \right ) \]

2724

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = t^{2} \sin \left (t \right ) \]

2725

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime } = t^{2} \]

2726

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+y = t +{\mathrm e}^{-t} \]

2727

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = t^{3} {\mathrm e}^{-t} \]

2835

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2836

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2837

\[ {}y^{\prime \prime }-\lambda y = 0 \]

2838

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2839

\[ {}y^{\prime \prime }-2 y^{\prime }+\left (\lambda +1\right ) y = 0 \]

2840

\[ {}y^{\prime \prime }+\lambda y = 0 \]

3059

\[ {}y^{\prime \prime }-4 y = 0 \]

3060

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 0 \]

3061

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

3062

\[ {}y^{\prime \prime }-7 y^{\prime }+6 y = 0 \]

3063

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

3064

\[ {}y^{\prime \prime }-2 y^{\prime }-y = 0 \]

3065

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

3066

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

3067

\[ {}2 y^{\prime \prime }+2 y^{\prime }-y = 0 \]

3068

\[ {}2 y^{\prime \prime \prime }-y^{\prime \prime }-2 y^{\prime }+y = 0 \]

3069

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }+12 y = 0 \]

3070

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+y^{\prime }+6 y = 0 \]

3071

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime }+8 y = 0 \]

3072

\[ {}y^{\prime \prime \prime }-7 y^{\prime }+6 y = 0 \]

3073

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

3074

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }-17 y^{\prime }+60 y = 0 \]

3075

\[ {}y^{\prime \prime \prime }-9 y^{\prime \prime }+23 y^{\prime }-15 y = 0 \]

3076

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-7 y^{\prime \prime }-y^{\prime }+6 y = 0 \]

3077

\[ {}2 y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }-20 y^{\prime \prime }+27 y^{\prime }+18 y = 0 \]

3078

\[ {}12 y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }-3 y^{\prime \prime }+y^{\prime } = 0 \]

3079

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+3 y^{\prime } = 0 \]

3080

\[ {}4 y^{\prime \prime \prime }+2 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

3081

\[ {}y^{\prime \prime \prime }-5 y^{\prime \prime }-2 y^{\prime }+24 y = 0 \]

3082

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-7 y^{\prime \prime }-8 y^{\prime }+12 y = 0 \]

3083

\[ {}y^{\left (5\right )}-3 y^{\prime \prime \prime \prime }-5 y^{\prime \prime \prime }+15 y^{\prime \prime }+4 y^{\prime }-12 y = 0 \]

3084

\[ {}y^{\left (5\right )}+y^{\prime \prime \prime \prime }-13 y^{\prime \prime \prime }-13 y^{\prime \prime }+36 y^{\prime }+36 y = 0 \]

3085

\[ {}y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }-15 y^{\prime \prime \prime }-19 y^{\prime \prime }+30 y^{\prime } = 0 \]

3086

\[ {}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-4 y = 0 \]

3087

\[ {}y^{\left (5\right )}+3 y^{\prime \prime \prime }+2 y^{\prime } = 0 \]

3088

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

3089

\[ {}y^{\prime \prime } = 0 \]

3090

\[ {}2 y^{\prime \prime \prime }+y^{\prime \prime }-4 y^{\prime }-3 y = 0 \]

3091

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0 \]

3092

\[ {}y^{\prime \prime \prime \prime } = 0 \]

3093

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = 0 \]

3094

\[ {}4 y^{\prime \prime \prime }-3 y^{\prime }+y = 0 \]

3095

\[ {}4 y^{\left (5\right )}-3 y^{\prime \prime \prime }-y^{\prime \prime } = 0 \]

3096

\[ {}y^{\prime \prime \prime }-7 y^{\prime \prime }+16 y^{\prime }-12 y = 0 \]

3097

\[ {}4 y^{\prime \prime \prime }-8 y^{\prime \prime }+5 y^{\prime }-y = 0 \]

3098

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

3099

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

3100

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = 0 \]

3101

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime }-20 y = 0 \]

3102

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+6 y = 0 \]

3103

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+6 y^{\prime \prime }-8 y^{\prime }+8 y = 0 \]

3104

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }-6 y^{\prime }+2 y = 0 \]

3105

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }-4 y = 0 \]

3106

\[ {}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+10 y^{\prime }-15 y = 0 \]

3107

\[ {}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+11 y^{\prime }-40 y = 0 \]

3108

\[ {}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+4 y^{\prime \prime }-12 y^{\prime }+16 y = 0 \]

3109

\[ {}4 y^{\prime \prime \prime }+12 y^{\prime \prime }-3 y^{\prime }+14 y = 0 \]

3110

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime \prime }+6 y^{\prime \prime \prime }-6 y^{\prime \prime }+8 y^{\prime }-8 y = 0 \]

3111

\[ {}y^{\prime \prime }-4 y = 3 \cos \left (x \right ) \]

3112

\[ {}y^{\prime \prime }+y = \sin \left (2 x \right ) \]

3113

\[ {}y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{x} \]

3114

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{-2 x} \]

3115

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

3116

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2} \]

3117

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

3118

\[ {}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x} \]

3119

\[ {}y^{\prime \prime }-4 y = x +{\mathrm e}^{2 x} \]

3120

\[ {}y^{\prime \prime }-9 y = {\mathrm e}^{3 x}+\sin \left (3 x \right ) \]

3121

\[ {}y^{\prime \prime }-y^{\prime }-6 y = x^{3} \]

3122

\[ {}-2 y^{\prime \prime }+3 y = x \,{\mathrm e}^{x} \]

3123

\[ {}y^{\prime \prime }+4 y = x \sin \left (x \right ) \]

3124

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime } = x^{2}+8 \]

3125

\[ {}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{x} \sin \left (3 x \right ) \]

3126

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-12 y = x +{\mathrm e}^{2 x} \]

3127

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+y^{\prime }-4 y = {\mathrm e}^{4 x} \sin \left (x \right ) \]

3128

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = x^{3} {\mathrm e}^{2 x} \]

3129

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{2 x} x \]

3130

\[ {}y^{\prime \prime \prime \prime }+2 n^{2} y^{\prime \prime }+n^{4} y = \sin \left (k x \right ) \]

3131

\[ {}y^{\prime \prime }+2 n y^{\prime }+n^{2} y = 5 \cos \left (6 x \right ) \]

3132

\[ {}y^{\prime \prime }+9 y = \left (1+\sin \left (3 x \right )\right ) \cos \left (2 x \right ) \]

3133

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 2 x -{\mathrm e}^{-4 x}+\sin \left (2 x \right ) \]

3134

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime } = \left (2 x^{2}+x \right ) {\mathrm e}^{-2 x}+5 \cos \left (3 x \right ) \]

3135

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (x \right )^{2} \]

3136

\[ {}y^{\prime \prime \prime \prime }+4 y = 5 \,{\mathrm e}^{2 x} \sin \left (3 x \right ) \]

3137

\[ {}y^{\prime \prime }-5 y^{\prime }-6 y = {\mathrm e}^{3 x} \]

3138

\[ {}y^{\prime \prime }+4 y = 12 \cos \left (x \right )^{2} \]

3139

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

3140

\[ {}y^{\prime \prime }+y = {\mathrm e}^{x} \sin \left (x \right ) \]

3141

\[ {}2 y^{\prime \prime }+y^{\prime } = 8 \sin \left (2 x \right )+{\mathrm e}^{-x} \]

3142

\[ {}y^{\prime \prime }+y = 3 x \sin \left (x \right ) \]

3143

\[ {}2 y^{\prime \prime }+5 y^{\prime }-3 y = \sin \left (x \right )-8 x \]

3144

\[ {}8 y^{\prime \prime }-y = x \,{\mathrm e}^{-\frac {x}{2}} \]

3145

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

3146

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{x} \]

3147

\[ {}y^{\prime \prime }+4 y = x^{2} \]